Spill the beans - Mlynowski, Sarah (New York Scholastic Press, 2019)
Abby and Jonah take a trip through the magic mirror and finally end up in Jack and the beanstalk (which happens to be Jonah's favorite story ever)--but things soon start to go wrong, and the children have to try and set the tale right, even if it means trading their dog, Prince, for the magic beans, climbing the beanstalk (three times!), and reaching an amicable settlement with the giants (Magnus and Philippa, who are really quite nice), and the sneaky trader, Devin, to get their dog back.
450
008-011.
Accelerated Reader
Keywords: Jack and the beanstalk; Humorous fiction; Siblings -- Fiction; Giants -- Fiction; Magic -- Fiction; Fairy tales -- Fiction; Characters and characteristics in literature -- Fiction; JUV019000 -- FICTION / Humorous Stories; JUV013000 -- FICTION / Family / General; JUV012030 -- FICTION / Fairy Tales & Folklore / General; Humorous fiction; Domestic fiction; Fairy tales